Análise do Aproveitamento da energia eólica no Brasil - Telles, Chrsitiano Ventura venâncio (2015)
The use of wind as a means for electricity generation around the world has contributed to increase the installed power generation capacity, providing greater supply safety and security to meet new consumption demands. Added to this, another contribution of the use of wind energy is the reduction of environmental damage resulting from the consumption of energy generated by non-renewable sources and pollutants, such as oil and coal. The available wind power generation potential in Brazil is more than 143 GW, however only 2.11 GW are currently utilized, corresponding to only 1.47% of the available potential. This thesis aims to clarify the reason of a so little use, identifying the main factors which contribute to the low utilization of the wind power potential in Brazil. For this purpose, used the fundamentals of the Grounded Theory method based on a literature review of the available wind power potential, its recent developments, expansion regulatory policies, costs analysis confronting all these same dimensions mith expert opinions collected by a questionnaire. Even with an immense available potential, one can conclude that the Brazilian electric sector management presents a series of factors such as regulatory barriers, little technology knowledge, poor supply chain management, environmental licensing barriers, which hinder the widespread use of wind power in Brazil.